Real time analysis of an intelligent torque controller for a hybrid bicycle - Indulal, S; Ushakumari, S; S. Chandramohanan Nair, P (International Journal of Engineering and Technology, 2018)
Most of the means of transportation is based on Internal Combustion engines, since they are fast and furious means of transportation. But bicycles are also relevant nowadays since they are the ideal means of the short commutation and which also helps in improving the human health by serving as a work out machine. But in our busy life bicycles are not preferred due to the uneven terrains. Electric bikes are the solution for this issue. Pedal assist sensor (PAS) based hybrid bicycle are also available, which will intermittently turn on and control the speed of electric drive based on the pedal crank speed. Thus there the electric drive assistance will be provided based on the speed of the pedal cranking. The real assistance should be provided when our torque requirement is needed. This paper deal with a novel sensor which sends the effort required at the pedal by the rider and intelligently control the electric drive so as to meet the required torque. The advantage of this controller is that the rider need to give only the same effort at the pedal irrespective of the terrain variations for a constant speed ride. A Fuzzy Logic Controller (FLC) is proposed here. The performance of the controller is simulated and analysed with the experimental results to prove the efficacy of the proposed technique.